2010
DOI: 10.1016/j.jcrs.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Achromobacter xylosoxidans keratitis after laser in situ keratomileusis

Abstract: A 31-year-old man was referred to us 2 months after bilateral laser in situ keratomileusis (LASIK). On presentation, the corrected distance visual acuity was hand motion in the right eye and 20/25 in the left eye. Slitlamp examination showed a diffuse central stromal infiltrate, flap melting, and hypopyon in the right eye and marked interface opacities with crystal-like edges in the left eye. Flap lift and irrigation were performed. Because of the progressive keratitis, penetrating keratoplasty (PKP) was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…A. xylosoxidans has been isolated in cases of ear and eye infections (26,28,30), urinary tract infections (28,38), intra-abdominal infections (39), liver abscesses (4), soft tissue infections (5, 29), osteomyelitis (42), arthroplasty infections (37), meningitis (8,26,29,30), ventriculitis (35), endocarditis (1, 2, 41), and pneumonia (3, 10-13, 20, 32, 34, 39, 44). A. xylosoxidans has been isolated from multiple sources, including blood (3,9,11,16,18,28,33), cerebrospinal fluid (CSF) (8,26,29,30), stool, urine (28,38), sputum (40), skin, ear discharge (29,45), wounds (29), abscesses (4, 39), bone (42), joints (37), endocardium (1, 2, 41), ascites fluid (39), and corneal scrapings and vitreous humor fluid (14,22,27,31).…”
Section: Case Reportmentioning
confidence: 99%
“…A. xylosoxidans has been isolated in cases of ear and eye infections (26,28,30), urinary tract infections (28,38), intra-abdominal infections (39), liver abscesses (4), soft tissue infections (5, 29), osteomyelitis (42), arthroplasty infections (37), meningitis (8,26,29,30), ventriculitis (35), endocarditis (1, 2, 41), and pneumonia (3, 10-13, 20, 32, 34, 39, 44). A. xylosoxidans has been isolated from multiple sources, including blood (3,9,11,16,18,28,33), cerebrospinal fluid (CSF) (8,26,29,30), stool, urine (28,38), sputum (40), skin, ear discharge (29,45), wounds (29), abscesses (4, 39), bone (42), joints (37), endocardium (1, 2, 41), ascites fluid (39), and corneal scrapings and vitreous humor fluid (14,22,27,31).…”
Section: Case Reportmentioning
confidence: 99%
“…Serratia marcesens has been reported as a cause of microbial keratitis after PRK [27] and LASIK [28]. Bilateral Achromobacter xylosoxidans post-LASIK keratitis was reported as a polymicrobial infection in association with Aspergillus and coagulase-negative staphylococcal infection [29]. This patient required bilateral corneal grafts to control the infection.…”
Section: Gram-negative Organismsmentioning
confidence: 88%
“…In their study, the symptoms of all patients except one were resolved with topical antibiotic therapy. Linke et al [24] also reported a case of bilateral Achromobacter xylosoxidans keratitis after LASIK.…”
Section: Discussionmentioning
confidence: 99%